KAJIAN DOSIS BAKTERI FOTOSINTETIK DAN ZPT TERHADAP PERTUMBUHAN DAN HASIL PADI (Oryza sativa. L): Inpari 32, Dosis, Bakteri Fotosintetik, ZPT - Benhar Aslam; Siswadi, Siswadi; Bahri, Saiful; Sigit Saputro, Avisema (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2023)
This study entitled Study of Dosage of Photosynthetic Bacteria and PGR on the Growth and Yield of Rice (Oryza sativa. L) with the aim of examining how much influence photosynthetic bacteria dosage and PGR dose have on the growth and yield of Rice plants. This research implemented in the paddy fields of Dukuh Beji Wetan, Kemiri Village, Kebakkramart District, Karanganyar Regency. The experiment was carried out on August 28 – December 11, 2022. The experimental design used in this study was a Completely Randomized Block Design with 2 treatment factors and repeated 3 times. The use of photosynthetic bacteria (P) as a factor 1 consists of 4 levels, namely: P0= 0 ml/l, P1= 5 ml/l, P2= 10 ml/l, P3= 15 ml/l. PGR (Z) as factor 2 consists of 3 levels namely: Z0 = 0 ml/l, Z1= 5 ml/l, Z2= 10 ml/l. Data analysis used analysis of variance followed by further tests of multiple linear regression. The results showed that the dose of photosynthetic bacteria and ZPT had an effect on rice plants. But in several observation parameters for the best recommended dose it is not known with certainty so it is advisable to carry out further tests.